HUBUNGAN ANTARA KECERDASAN EMOSI DAN PROBLEM FOCUS COPING DENGAN PERILAKU DELINKUEN PADA SISWA SMP - Alam Purwandhani Prastuti; Taufik Taufik (Universitas Muhammadiyah Surakarta, 2014)
The aim of this research is to identify the relationship between the emotional intelligence and problem focus coping with delinquent behaviour of Junior High School students. The major hypothesis proposed is “There is relationship between emotional intelligence and problem focus coping with delinquent behaviour on Junior High School students”. The minor hypotheses are as follows: (a) there is negative relationship between intelligence emotional with delinquent behaviour on Junior High School students; (b) there is negative relationship between problem focus coping with delinquent behaviour on Junior High school students. The subjects of this research are students of Muhammadiyah 1 Surakarta Junior High School grade VIIIA, VIIID, and VIIIE, consisting of 98 students. Data sampling used is cluster random sampling ada data collect ing technique used is emotional intelligence scale and problem focus coping and delinquent behaviour scale. Data analysis techniques uses is regression analysis. The result indicates taht there is negative relationship between emotional intelligence and problem focus coping with delinquent behaviour on Junior High School students. The effective contribution of emotional intelligence toward delinquent behaviour is 12%. The effecttive contribution of problem focus coping toward delinquent behaviour is 9%. The emotional intelligence on research subject is moderate; likewise the variable of problem focus coping dan delinquent behaviour is moderate as well.